A Novel Approach of Potent Antioxidant and Antimicrobial Agents Containing Coumarin Moiety Accompanied with Cytotoxicity Studies on the Newly Synthesized Derivatives - Huda R. M. Rashdana, Sami M. Nasrb, Heba A. El-Refaia, Mohamed S. Abdel-Azizc (Journal of Applied Pharmaceutical Science, 2017)
3-Amino-6-(2-oxo-2H-chromen-3-yl)pyridine-2-carbonitrile (2) was synthesized via the reaction of 3-(dimethylamino)acryloyl-2H-chromen-2-one (1) with malononitrile. The reactivity of the 2-amino-3-cyanopyridine derivative 2 toward a variety of electrophiles as triethylorthoformate followed by nitrogenous nucleophiles as hydrazine hydrate was investigated. Also, enamine 1 was utilized as precursor for synthesis of new 3-heteroarylsubstituted coumarins, in which it reacted with a series of hydrazonoyl halides and p-bromobenzenediazonium chloride to yield different3-substituted coumarins. The structures of the newly synthesized derivatives were confirmed by different spectral tools (IR, H1NMR, mass spectrometry and elemental analysis). All the newly synthesized compounds were screened for their antioxidant, antimicrobial activities and cytotoxicity. The preliminary structure-activity relationship was discussed to illustrate the essential structure requirements.
Keywords: Coumarins, enamines, antioxidant agents, antimicrobial agents and cytotoxicity.